Islamic Religious Education Teacher Efforts in Increasing Students Interest in Reading the Quran - Yemmardotillah, M; Yusnihar, Yusnihar; Syamsuardi, Syamsuardi (Ahlussunnah: Journal of Islamic Education, 2022)
The aim of this research is to determine the reading interest of Class VII students at the Legusa Community Learning Activity Center, Luak District, Lima Puluh Kota Regency, and the efforts of Islamic Religious Education teachers in increasing students' interest in reading the Qur'an, as well as to determine the supporting and inhibiting factors. which influences the efforts of Islamic Religious Education teachers to increase students' interest in reading the Quran. This research uses descriptive qualitative methods. Data was collected through observation, interviews, and documentation. The data analysis uses the following steps, namely data reduction, data display, and drawing conclusions. The results of the analysis show the condition of interest in reading the Quran of class VII students at the Legusa Community Learning Activity Center, Luak District, Kab. Fifty Cities showed results that students' interest in reading the Quran was still low. The efforts carried out by Islamic Religious Education teachers are quite diverse. Starting from motivating students to be enthusiastic and happy when studying the Quran. Gives an overview of the virtues of reading the Quran. Give rewards to students who are serious about studying. Tadarus at the beginning of learning. Factors that influence Islamic Religious Education teachers increasing interest in reading the Quran are factors within students, namely physiological and psychological factors in children. Factors from outside the student, the student's family, and their environment. lack of available lesson hours.